Pengaruh Edukasi Gizi Dengan Video Learning Multimedia terhadap Peningkatan Pengetahuan dan Sikap Healthy Food Choice pada Remaja Putri untuk mencegah Overweight di SMAN 1 Malunda - Nuramilah; Nurpatwa Wilda Ningsi; Wahdaniyah; Bazrul Makatita (Nutrition Science and Health Research, 2024)
This research was motivated by the unhealthy food choices of young women due to a lack of knowledge about healthy food choices and the increasing rate of overweight due to food choices. This research aims to determine the effect of nutrition education on increasing knowledge and attitudes towards healthy food choices in young women to prevent overweight with multimedia video learning. The method used is a quantitative design using pre-experimental design with a one group pretest-posttest approach and probability stratified random sampling technique. The research population was 263 female students and the research sample was 96 female students. Knowledge and attitude data were collected using a questionnaire, and analyzed using the Wilcoxon test and paired t-test. The research results showed that there was an increase in the average value of knowledge from 30.10 to 82.60. Meanwhile, the average attitude value was originally 61.43 to 80.48. Based on the analysis test carried out, there is a significant value for knowledge and attitudes, namely 0.000, which means <0.05, it can be concluded that there is a significant influence of providing nutrition education using multimedia video learning on increasing the knowledge and attitudes of young women about healthy food choices to prevent overweight.